Thermal Comfort And Its Relation To Ventilation Approaches In Mosques - Zakaria, Muhammad Norshazril Alif (Universiti Sains Malaysia, 2017)
Thermal comfort is the study of indoor comfort level of the occupant in indoor space. This project present the study of thermal comfort that had been carried out in mosque building around Nibong Tebal, Penang, Malaysia. The objective of the study includes determining the compliance level of thermal comfort parameters (relative humidity, temperature and air speed) with relevant standard and establish relationship between ventilation system with Predicted Mean Vote (PMV) and Predicted Percentage Dissatisfied (PPD) according to ASHRAE Standard-55. The study was conducted at 6 mosque building from 12:00 p.m. to 5:00 p.m. In order to asses thermal condition during Zohor/Jumaat and Asar prayer times. During prayer time, active ventilation was switched on meanwhile before and after prayer time only passive ventilation (window and door) available. The result show the highest value for temperature, relative humidity and air speed that being recorded are 34.4 °C, 78.5% and 1.24 m/s which does not comply with Industrial Code of Practice 2010. The acceptable range for temperature is 23°C-26ºC, relative humidity is 40%-70% and air speed is 0.15-0.5 m/s. Furthermore, the temperature build up rapidly before and after prayer time because only passive ventilation was available at that time. Meanwhile, the temperature drop during prayer because during that time, active ventilation such as fans and air conditioner were switched on. Overall observation found that better thermal comfort was during prayer time and environmental sensation condition of the mosque is slightly warm and warm. Moreover, according to result that being recorded and calculated to identity the thermal comfort in mosque building, most mosque building did not provide a good thermal comfort and most of number of occupant dissatisfied is also high.